2014
DOI: 10.1002/etc.2704
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydroxylated multiwalled carbon nanotubes on the toxicity of nickel to Daphnia magna under different pH levels

Abstract: Hydroxylated multiwalled carbon nanotubes (OH-MWCNTs), with large amounts of hydrophilic groups attached on the nanoparticle surface, have caused considerable concern because of their inevitable release into aquatic environments. They may interact with other contaminants such as heavy metals and even influence their toxicity, fate, and transport. In the present study, the stability of OH-MWCNTs suspended in aerated Nanjing tap water (moderately hard) was evaluated using the spectrophotometric method. The toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(53 reference statements)
5
12
0
Order By: Relevance
“…Therefore, the presence of OH‐MWCNTs could enhance the toxicity of arsenic. The results were consistent with those reported by other researchers .…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Therefore, the presence of OH‐MWCNTs could enhance the toxicity of arsenic. The results were consistent with those reported by other researchers .…”
Section: Resultssupporting
confidence: 94%
“…It was found that stability was reduced during the exposure period, and the CNT solutions with higher concentrations had lower stabilities. This was consistent with experimental results for OH‐MWCNTs .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It was also reported that, traditional carbon nanomaterials (carbon nanotubes and nC 60 ) increased the toxicity of heavy metal ions in D. magna by adsorbing metal ions and increasing metals accumulation as carriers. 23,24 Although GO is also a kind of carbon nanomaterial, its effect on biotoxicity of heavy metal ions may be a totally different case. According to Yu and Wang, although the physical properties of different carbon nanomaterials were similar in some ways, their inuences on metals accumulation and biotoxicity depend largely on the chemical properties.…”
Section: Introductionmentioning
confidence: 99%